2021
DOI: 10.3390/rs13040561
|View full text |Cite
|
Sign up to set email alerts
|

Using Time Series Sentinel-1 Images for Object-Oriented Crop Classification in Google Earth Engine

Abstract: The purpose of this study was to evaluate the feasibility and applicability of object-oriented crop classification using Sentinel-1 images in the Google Earth Engine (GEE). In this study, two study areas (Keshan farm and Tongnan town) with different average plot sizes in Heilongjiang Province, China, were selected. The research time was two consecutive years (2018 and 2019), which were used to verify the robustness of the method. Sentinel-1 images of the crop growth period (May to September) in each study area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 60 publications
1
44
1
Order By: Relevance
“…When comparing examples of crops classifications using X-band and C-band SAR data, it should be first mentioned that each study has unique features, including the SAR data available and the number and type of crops present. In this study, and in terms of overall accuracy, the results obtained from the experiments using only eight PAZ and eight S1 images were not as good as expected with regard to previous results found in the literature with time series of X-and C-band SAR data [23,[41][42][43][44]. For comparison purposes, the OA and kappa values obtained in all five experiments are depicted in Figure 6.…”
Section: Discussioncontrasting
confidence: 50%
“…When comparing examples of crops classifications using X-band and C-band SAR data, it should be first mentioned that each study has unique features, including the SAR data available and the number and type of crops present. In this study, and in terms of overall accuracy, the results obtained from the experiments using only eight PAZ and eight S1 images were not as good as expected with regard to previous results found in the literature with time series of X-and C-band SAR data [23,[41][42][43][44]. For comparison purposes, the OA and kappa values obtained in all five experiments are depicted in Figure 6.…”
Section: Discussioncontrasting
confidence: 50%
“…(2) SAR + optical RS images for better model performance: In addition, many studies reported [17,57,68,72,74,165,166,182,212,214] or suggested in future work [46,56,107,215] that SAR combined with optical RS images would improve model performance. Three classification methods (SVM, RF, and decision fusion) were used in [52] for the pixel-wise classification for crop mapping.…”
Section: Feature Engineering and Feature Importancementioning
confidence: 99%
“…However, it is often blocked by clouds limiting its utility. SAR imagery works day or night regardless of cloud cover, so [74] used it for crop classification while testing input composite image length and ML classification performance. The authors compared an object-oriented classification method combining the SNIC algorithm with a RF with that of a pixel-based method of just the RF by itself.…”
Section: Appendix a The Accompanying Interactive Web App Tool For The...mentioning
confidence: 99%
“…Although Landsat images have proven useful for mapping agricultural fields over large areas, the spatial resolution of 30 m is often unable to resolve individual agricultural fields thereby inhibiting field-based applications in many cropping systems around the world [28]. Building on the experiences of the Landsat and SPOT missions, Sentinel-2 (S2) was designed within the framework of the European Copernicus program for land surface and agriculture monitoring [28] at a temporal resolution of 5 days and a spatial resolution of 10 m. As opposed to optical sensors, which are inhibited by clouds, Sentinel-1 (S1), which is also part of the Copernicus program enables the continuous monitoring of the earth's surface in all weather conditions at a temporal resolution of 6 days and a spatial resolution of 20 m. Various researchers have used S1 [29], [30], and predominantly S2 [31]- [40] for segmenting agricultural fields. In using the S1 or S2 images, most of those authors used existing segmentation algorithms (e.g., [29], [30], [32]- [34], [36]- [40]), some proposed new segmentation algorithms (e.g., [31], [35]), and others proposed new segmentation parameter optimization approaches (e.g., [36], [37]).…”
Section: Introductionmentioning
confidence: 99%
“…Building on the experiences of the Landsat and SPOT missions, Sentinel-2 (S2) was designed within the framework of the European Copernicus program for land surface and agriculture monitoring [28] at a temporal resolution of 5 days and a spatial resolution of 10 m. As opposed to optical sensors, which are inhibited by clouds, Sentinel-1 (S1), which is also part of the Copernicus program enables the continuous monitoring of the earth's surface in all weather conditions at a temporal resolution of 6 days and a spatial resolution of 20 m. Various researchers have used S1 [29], [30], and predominantly S2 [31]- [40] for segmenting agricultural fields. In using the S1 or S2 images, most of those authors used existing segmentation algorithms (e.g., [29], [30], [32]- [34], [36]- [40]), some proposed new segmentation algorithms (e.g., [31], [35]), and others proposed new segmentation parameter optimization approaches (e.g., [36], [37]). One area that is yet to be comprehensively explored is the determination of the optimal feature set from S1 and S2 images for segmenting agricultural fields given that both sensors come with different bands and additional features like band indices can be calculated as well.…”
Section: Introductionmentioning
confidence: 99%